Efektivitas Sistem Informasi Akuntansi Atas Pendapatan Jasa Penitipan Barang Pada PT. Pegadaian (Persero) UPS Sibuhuan - Fatwa, M. Ihsan; Sudiarti, Sri; Kusmilawaty, Kusmilawaty (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
One of the information systems that is really needed in companies, without good information, company management will experience difficulties in making decisions. The information system needed in a company is an accounting information system, because basically an Accounting Information System (AIS) is a system that processes data and transactions to produce information that is useful for planning, controlling and operating a business. This research aims to analyze the effectiveness of information systems. Accounting for Revenue from Goods Safekeeping Services at PT. Pegadaian (Persero) UPS Sibuhuan. The research method used in this research is descriptive qualitative with a field approach through interviews and documentation, then analysis is carried out. The results of this research indicate that the accounting information system for goods deposit services revenue has been implemented effectively at PT Pegadaian (Persero) UPS Sihubuan. PT Pegadaian (Persero) UPS Sihubuan uses source documents to collect initial data about business activities, and then transfers the data to a computer. With well-designed source documents, data entry can be used properly for speed in recording business activities. When data about business activities has been collected, the next step is the process of updating previously stored information about the resources affected by these activities. The updating process is carried out directly, transactions occur and then produce output, namely financial reports. There is an accounting information system reporting process for deposit service revenues in the form of recognition, measurement, disclosure, reporting and accounting report notes.